ARCHAEOLOGICAL STUDY ON GUANCAS AND TARAMAS. A NEW ANALYSIS OF THE ECONOMIC AND SOCIAL DEVELOPMENT OF THESE CULTURES IN CENTRAL ANDES - Navarro Amaro, Irvin (2014)
In this paper we carry out a comprehensive archaeological study on the Pre-Tawantinsuyo guancas and taramas, focusing on their economic and social development. For this purpose, we performed methodical archaeological surveys and excavations, which gave us much empirical evidence. The description and analysis of this data helped us to better understand these cultures in relation to the Central Andes. Therefore, on this basis, we propose new theories that better explain the economic and social development of Guancas and taramas, likewise, we present a critique of the theories previously proposed by Parsons and the Upper Mantaro Research Project (UMARP). Furthermore, in this paper, we conduct a brief study on the funerary activities of the Guanca and Tarama, a subject little studied so far.